TRAINING PROFESSIONALS SOCIAL SPHERE TO EMERGENCY ASSISTANCE CRISIS POPULATIONS - Албул, О. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article deals with one aspect of the process of preparation of experts of social sphere to provide emergency crisis populations, including the formation of the cognitive component of professional readiness on the role of integrated social services to provide emergency social assistance, including highlights framework for early intervention services based on state standards of social services and emergency crisis intervention; presented information on the emergency telephone counseling through the activities of the specialized formation of «hotline»